Post-war reconstruction of theatrical buildings: 1945–2020 - Anisimov, Alexander (project baikal, 2021)
During the reconstruction of theatres of national significance after the World War II it was revealed that the most valuable monuments of theatrical architecture were damaged by bombing. The article studies the three stages of the post-war reconstruction of such buildings in different European countries, including the USSR. At the turn of the 21st century, different countries launched a significant renovation of the worn-out architecture and a radical change in its characteristics. The author points to the best theatres of Russia, La Scala, Semper Opera House, Warsaw Grand Theatre and other examples.